How to make a recursive call with a decreasing argument? - coq

Inductive bar {X : Type} : list X -> Prop :=
| bar_nil : bar []
| bar_fst : forall x l, bar (rev l ++ l) -> bar (rev l ++ [x] ++ l)
| bar_snd : forall x l, bar (rev l ++ [x] ++ l) -> bar (rev l ++ [x; x] ++ l).
Axiom bar_surround :
forall X x (l : list X),
bar l -> bar ([x] ++ l ++ [x]).
Inductive list_last {X : Type} : list X -> Prop :=
| ll_nil : list_last []
| ll_snoc : forall l x, list_last l -> list_last (l ++ [x]).
Axiom ll_app :
forall X (a b : list X),
list_last a -> list_last b -> list_last (a ++ b).
Axiom ll_from_list :
forall {X} (l : list X),
list_last l.
Axiom app_head_eq :
forall X (a b c : list X),
a ++ c = b ++ c -> a = b.
Theorem foo :
forall X (l: list X), l = rev l -> bar l.
Proof.
intros.
induction l.
- constructor.
- assert (Hll := ll_from_list l).
inversion Hll.
+ apply (bar_fst x []). apply bar_nil.
+ rewrite <- H1 in H.
simpl in H.
rewrite rev_app_distr in H.
rewrite <- app_assoc in H.
simpl in H.
inversion H.
apply app_head_eq in H4.
apply bar_surround.
1 subgoal
X : Type
x : X
l, l0 : list X
x0 : X
H : x :: l0 ++ [x0] = x0 :: rev l0 ++ [x]
IHl : l = rev l -> bar l
Hll : list_last l
H0 : list_last l0
H1 : l0 ++ [x0] = l
H3 : x = x0
H4 : l0 = rev l0
______________________________________(1/1)
bar l0
I am only a step away from getting this exercise solved, but I do not know how to do the induction step. Note that IHl is useless here and replacing induction on l with induction on Hll would have a similar problem. In both cases, the inductive hypothesis would expect a call with a one step decrease while I need two - one with the item taken from both the start and the end of the list on both sides of the equality.
Consider that the type of the function I am trying to prove is forall X (l: list X), l = rev l -> bar l and I have l0 = rev l0 -> bar l0 in the goal here. l0 is a decreased argument thereby making the recursive call safe.
What should I do here?

You can prove the following inductive predicate:
Inductive delist {A : Type} : list A -> Prop :=
| delist_nil : delist []
| delist_one x : delist [x]
| delist_cons x y l : delist l -> delist (x :: l ++ [y])
.
Theorem all_delist {A} : forall xs : list A, delist xs.
Then in your final theorem, induction on delist xs will split into the cases you need.
Another solution is by strong induction on the length of the list:
Lemma foo_len X : forall (n : nat) (l: list X), length l <= n -> l = rev l -> bar l.
Proof.
induction n.
(* Nat.le_succ_r from the Arith module is useful here *)
...
Qed.
(* Final theorem *)
Theorem foo X : forall (l : list X), l = rev l -> bar l.
Proof.
intros; apply foo_len; auto.
Qed.
This is a more common and systematic principle than delist, but you will need to work more than the ad-hoc inductive type above to use the induction hypothesis in the main proof.

Here is how to implement the first part of what was suggested in the other answer. I can confirm that with this, solving the exercise is quite simple. That having said, I am interested how to solve the above using straightforward induction. Having to implement delist and its functions is more complicated than I'd prefer.
Inductive delist {A : Type} : list A -> Prop :=
| delist_nil : delist []
| delist_one x : delist [x]
| delist_wrap x y l : delist l -> delist (x :: l ++ [y]).
Theorem delist_cons {A} :
forall x (l : list A),
delist l -> delist (x :: l).
Proof.
intros.
generalize dependent x.
induction H; intros.
- constructor.
- replace [x; x0] with (x :: [] ++ [x0]).
2 : { reflexivity. }
+ apply delist_wrap with (l := []). constructor.
- replace (x0 :: x :: l ++ [y]) with (x0 :: (x :: l) ++ [y]).
2 : { reflexivity. }
constructor.
apply IHdelist.
Qed.
Theorem delist_from_list {A} :
forall l : list A,
delist l.
Proof.
induction l.
- constructor.
- assert (ll := ll_from_list l).
destruct ll.
+ constructor.
+ apply delist_cons. assumption.
Qed.

Related

Coq prove a false list assumption

Given the next theorem.
Theorem rev_injective_helper : forall (l : natlist) (n : nat),
[] = l ++ [n] -> False.
Proof.
intros l n H.
unfold app in H.
induction l. all: inversion H.
Qed.
How to prove the next goal?
1 subgoal
n : nat
l2 : natlist
H : [ ] = rev l2 ++ [n]
IHl2 : [ ] = rev l2 -> [ ] = l2
______________________________________(1/1)
[ ] = n :: l2
As I understand an assumption in this case is wrong H : [ ] = rev l2 ++ [n] how to finis the proof? Thanks in advance!
Update.
Missing definitions:
Fixpoint app (l1 l2 : natlist) : natlist :=
match l1 with
| nil ⇒ l2
| h :: t ⇒ h :: (app t l2)
end.
Notation "x ++ y" := (app x y)
(right associativity, at level 60).
Fixpoint rev (l:natlist) : natlist :=
match l with
| nil ⇒ nil
| h :: t ⇒ rev t ++ [h]
end.
I'm trying to prove this theorem:
Theorem rev_injective : forall (l1 l2 : natlist),
rev l1 = rev l2 -> l1 = l2.
As you say you have a false hypothesis in your context, so it doesn't matter what your are trying to prove, it will follow from falsehood.
To exploit this you can use the exfalso tactic which replaces your current goal by False. Then you should be able to conclude from rev_injective_helper and H no?

Equality between functional and inductive definitions

I have an inductive definition of the proposition P (or repeats l) that a lists contains repeating elements, and a functional definition of it's negation Q (or no_repeats l).
I want to show that P <-> ~ Q and ~ P <-> Q. I have been able to show three of the four implications, but ~ Q -> P seems to be different, because I'm unable to extract data from ~Q.
Require Import List.
Variable A : Type.
Inductive repeats : list A -> Prop := (* repeats *)
repeats_hd l x : In x l -> repeats (x::l)
| repeats_tl l x : repeats l -> repeats (x::l).
Fixpoint no_repeats (l: list A): Prop :=
match l with nil => True | a::l' => ~ In a l' /\ no_repeats l' end.
Lemma not_no_repeats_repeats: forall l, (~ no_repeats l) -> repeats l.
induction l; simpl. tauto. intros.
After doing induction on l, the second case is
IHl : ~ no_repeats l -> repeats l
H : ~ (~ In a l /\ no_repeats l)
============================
repeats (a :: l)
Is it possible to deduce In a l \/ ~ no_repeats l (which is sufficient) from this?
Your statement implies that equality on A supports double negation elimination:
Require Import List.
Import ListNotations.
Variable A : Type.
Inductive repeats : list A -> Prop := (* repeats *)
repeats_hd l x : In x l -> repeats (x::l)
| repeats_tl l x : repeats l -> repeats (x::l).
Fixpoint no_repeats (l: list A): Prop :=
match l with nil => True | a::l' => ~ In a l' /\ no_repeats l' end.
Hypothesis not_no_repeats_repeats: forall l, (~ no_repeats l) -> repeats l.
Lemma eq_nn_elim (a b : A) : ~ a <> b -> a = b.
Proof.
intros H.
assert (H' : ~ no_repeats [a; b]).
{ simpl. intuition. }
apply not_no_repeats_repeats in H'.
inversion H'; subst.
{ subst. simpl in *. intuition; tauto. }
inversion H1; simpl in *; subst; intuition.
inversion H2.
Qed.
Not every type supports eq_nn_elim, which means that you can only prove not_no_repeats_repeats by placing additional hypotheses on A. It should suffice to assume that A has decidable equality; that is:
Hypothesis eq_dec a b : a = b \/ a <> b.

coq induction with passing in equality

I have a list with a known value and want to induct on it, keeping track of what the original list was, and referring to it by element. That is, I need to refer to it by l[i] with varying i instead of just having (a :: l).
I tried to make an induction principle to allow me to do that. Here is a program with all of the unnecessary Theorems replaced with Admitted, using a simplified example. The objective is to prove allLE_countDown using countDown_nth, and have list_nth_rect in a convenient form. (The theorem is easy to prove directly without any of those.)
Require Import Arith.
Require Import List.
Definition countDown1 := fix f a i := match i with
| 0 => nil
| S i0 => (a + i0) :: f a i0
end.
(* countDown from a number to another, excluding greatest. *)
Definition countDown a b := countDown1 b (a - b).
Theorem countDown_nth a b i d (boundi : i < length (countDown a b))
: nth i (countDown a b) d = a - i - 1.
Admitted.
Definition allLE := fix f l m := match l with
| nil => true
| a :: l0 => if Nat.leb a m then f l0 m else false
end.
Definition drop {A} := fix f (l : list A) n := match n with
| 0 => l
| S a => match l with
| nil => nil
| _ :: l2 => f l2 a
end
end.
Theorem list_nth_rect_aux {A : Type} (P : list A -> list A -> nat -> Type)
(Pnil : forall l, P l nil (length l))
(Pcons : forall i s l d (boundi : i < length l), P l s (S i) -> P l ((nth i l d) :: s) i)
l s i (size : length l = i + length s) (sub : s = drop l i) : P l s i.
Admitted.
Theorem list_nth_rect {A : Type} (P : list A -> list A -> nat -> Type)
(Pnil : forall l, P l nil (length l))
(Pcons : forall i s l d (boundi : i < length l), P l s (S i) -> P l ((nth i l d) :: s) i)
l s (leqs : l = s): P l s 0.
Admitted.
Theorem allLE_countDown a b : allLE (countDown a b) a = true.
remember (countDown a b) as l.
refine (list_nth_rect (fun l s _ => l = countDown a b -> allLE s a = true) _ _ l l eq_refl Heql);
intros; subst; [ apply eq_refl | ].
rewrite countDown_nth; [ | apply boundi ].
pose proof (Nat.le_sub_l a (i + 1)).
rewrite Nat.sub_add_distr in H0.
apply leb_correct in H0.
simpl; rewrite H0; clear H0.
apply (H eq_refl).
Qed.
So, I have list_nth_rect and was able to use it with refine to prove the theorem by referring to the nth element, as desired. However, I had to construct the Proposition P myself. Normally, you'd like to use induction.
This requires distinguishing which elements are the original list l vs. the sublist s that is inducted on. So, I can use remember.
Theorem allLE_countDown a b : allLE (countDown a b) a = true.
remember (countDown a b) as s.
remember s as l.
rewrite Heql.
This puts me at
a, b : nat
s, l : list nat
Heql : l = s
Heqs : l = countDown a b
============================
allLE s a = true
However, I can't seem to pass the equality as I just did above. When I try
induction l, s, Heql using list_nth_rect.
I get the error
Error: Abstracting over the terms "l", "s" and "0" leads to a term
fun (l0 : list ?X133#{__:=a; __:=b; __:=s; __:=l; __:=Heql; __:=Heqs})
(s0 : list ?X133#{__:=a; __:=b; __:=s; __:=l0; __:=Heql; __:=Heqs})
(_ : nat) =>
(fun (l1 l2 : list nat) (_ : l1 = l2) =>
l1 = countDown a b -> allLE l2 a = true) l0 s0 Heql
which is ill-typed.
Reason is: Illegal application:
The term
"fun (l l0 : list nat) (_ : l = l0) =>
l = countDown a b -> allLE l0 a = true" of type
"forall l l0 : list nat, l = l0 -> Prop"
cannot be applied to the terms
"l0" : "list nat"
"s0" : "list nat"
"Heql" : "l = s"
The 3rd term has type "l = s" which should be coercible to
"l0 = s0".
So, how can I change the induction principle
such that it works with the induction tactic?
It looks like it's getting confused between
the outer variables and the ones inside the
function. But, I don't have a way to talk
about the inner variables that aren't in scope.
It's very strange, since invoking it with
refine works without issues.
I know for match, there's as clauses, but
I can't figure out how to apply that here.
Or, is there a way to make list_nth_rect use
P l l 0 and still indicate which variables correspond to l and s?
First, you can prove this result much more easily by reusing more basic ones. Here's a version based on definitions of the ssreflect library:
From mathcomp
Require Import ssreflect ssrfun ssrbool ssrnat eqtype seq.
Definition countDown n m := rev (iota m (n - m)).
Lemma allLE_countDown n m : all (fun k => k <= n) (countDown n m).
Proof.
rewrite /countDown all_rev; apply/allP=> k; rewrite mem_iota.
have [mn|/ltnW] := leqP m n.
by rewrite subnKC //; case/andP => _; apply/leqW.
by rewrite -subn_eq0 => /eqP ->; rewrite addn0 ltnNge andbN.
Qed.
Here, iota n m is the list of m elements that counts starting from n, and all is a generic version of your allLE. Similar functions and results exist in the standard library.
Back to your original question, it is true that sometimes we need to induct on a list while remembering the entire list we started with. I don't know if there is a way to get what you want with the standard induction tactic; I didn't even know that it had a multi-argument variant. When I want to prove P l using this strategy, I usually proceed as follows:
Find a predicate Q : nat -> Prop such that Q (length l) implies P l. Typically, Q n will have the form n <= length l -> R (take n l) (drop n l), where R : list A -> list A -> Prop.
Prove Q n for all n by induction.
I do not know if this answers your question, but induction seems to accept with clauses. Thus, you can write the following.
Theorem allLE_countDown a b : allLE (countDown a b) a = true.
remember (countDown a b) as s.
remember s as l.
rewrite Heql.
induction l, s, Heql using list_nth_rect
with (P:=fun l s _ => l = countDown a b -> allLE s a = true).
But the benefit is quite limited w.r.t. the refine version, since you need to specify manually the predicate.
Now, here is how I would have proved such a result using objects from the standard library.
Require Import List. Import ListNotations.
Require Import Omega.
Definition countDown1 := fix f a i := match i with
| 0 => nil
| S i0 => (a + i0) :: f a i0
end.
(* countDown from a number to another, excluding greatest. *)
Definition countDown a b := countDown1 b (a - b).
Theorem countDown1_nth a i k d (boundi : k < i) :
nth k (countDown1 a i) d = a + i -k - 1.
Proof.
revert k boundi.
induction i; intros.
- inversion boundi.
- simpl. destruct k.
+ omega.
+ rewrite IHi; omega.
Qed.
Lemma countDown1_length a i : length (countDown1 a i) = i.
Proof.
induction i.
- reflexivity.
- simpl. rewrite IHi. reflexivity.
Qed.
Theorem countDown_nth a b i d (boundi : i < length (countDown a b))
: nth i (countDown a b) d = a - i - 1.
Proof.
unfold countDown in *.
rewrite countDown1_length in boundi.
rewrite countDown1_nth.
replace (b+(a-b)) with a by omega. reflexivity. assumption.
Qed.
Theorem allLE_countDown a b : Forall (ge a) (countDown a b).
Proof.
apply Forall_forall. intros.
apply In_nth with (d:=0) in H.
destruct H as (n & H & H0).
rewrite countDown_nth in H0 by assumption. omega.
Qed.
EDIT:
You can state an helper lemma to make an even more concise proof.
Lemma Forall_nth : forall {A} (P:A->Prop) l,
(forall d i, i < length l -> P (nth i l d)) ->
Forall P l.
Proof.
intros. apply Forall_forall.
intros. apply In_nth with (d:=x) in H0.
destruct H0 as (n & H0 & H1).
rewrite <- H1. apply H. assumption.
Qed.
Theorem allLE_countDown a b : Forall (ge a) (countDown a b).
Proof.
apply Forall_nth.
intros. rewrite countDown_nth. omega. assumption.
Qed.
The issue is that, for better or for worse, induction seems to assume that its arguments are independent. The solution, then, is to let induction automatically infer l and s from Heql:
Theorem list_nth_rect {A : Type} {l s : list A} (P : list A -> list A -> nat -> Type)
(Pnil : P l nil (length l))
(Pcons : forall i s d (boundi : i < length l), P l s (S i) -> P l ((nth i l d) :: s) i)
(leqs : l = s): P l s 0.
Admitted.
Theorem allLE_countDown a b : allLE (countDown a b) a = true.
remember (countDown a b) as s.
remember s as l.
rewrite Heql.
induction Heql using list_nth_rect;
intros; subst; [ apply eq_refl | ].
rewrite countDown_nth; [ | apply boundi ].
pose proof (Nat.le_sub_l a (i + 1)).
rewrite Nat.sub_add_distr in H.
apply leb_correct in H.
simpl; rewrite H; clear H.
assumption.
Qed.
I had to change around the type of list_nth_rect a bit; I hope I haven't made it false.

Coq: goal variable not transformed by induction when appearing on left side of arrow

I am trying to prove the following theorem by induction over l. It's an easy theorem on paper, however when I try to prove it in Coq I am not getting the induction goal I would expect.
Theorem nodup_app__disjoint: forall {X: Type} (l: list X),
(forall l1 l2 : list X, l = l1 ++ l2 -> Disjoint l1 l2) -> NoDup l.
Proof.
intros X l. induction l.
- intros F. apply nodup_nil.
- (* ??? *)
The state at this point:
1 subgoal
X : Type
x : X
l : list X
IHl : (forall l1 l2 : list X, l = l1 ++ l2 -> Disjoint l1 l2) -> NoDup l
______________________________________(1/1)
(forall l1 l2 : list X, x :: l = l1 ++ l2 -> Disjoint l1 l2) ->
NoDup (x :: l)
But that is not at all the goal I would expect! Shouldn't x :: l = l1 ++ l2 be replaced by l = l1 ++ l2?
Here are the propositions I'm working with, in case you'd like to reproduce the problem and see for yourself:
Inductive Disjoint {X : Type}: list X -> list X -> Prop :=
| disjoint_nil: Disjoint [] []
| disjoint_left: forall x l1 l2, Disjoint l1 l2 -> ~(In x l2) -> Disjoint (x :: l1) l2
| disjoint_right: forall x l1 l2, Disjoint l1 l2 -> ~(In x l1) -> Disjoint l1 (x :: l2).
Inductive NoDup {X: Type}: list X -> Prop :=
| nodup_nil: NoDup []
| nodup_cons: forall hd tl, NoDup tl -> ~(In hd tl) -> NoDup (hd :: tl).
But that is not at all the goal I would expect! Shouldn't x :: l = l1 ++ l2 be replaced by l = l1 ++ l2?
Short answer: It should not!
Induction principle for lists
Let's recall the induction principle for lists:
Check list_ind.
(*
list_ind
: forall (A : Type) (P : list A -> Prop),
P [] ->
(forall (a : A) (l : list A), P l -> P (a :: l)) ->
forall l : list A, P l
*)
It means that in order to prove that a predicate P holds for all lists (forall l : list A, P l), one needs to prove that
P holds for the empty list -- P [];
P holds for all non-empty lists, given that it holds for their tails -- (forall (a : A) (l : list A), P l -> P (a :: l)).
Applying the list induction principle to the goal
Now, we have the following goal:
(forall l1 l2, l = l1 ++ l2 -> Disjoint l1 l2) -> NoDup l.
To see what goals we should get when trying to prove the statement by induction on l, let's mechanically substitute l in the above with [] in one case and h :: tl the other.
[] case:
(forall l1 l2, [] = l1 ++ l2 -> Disjoint l1 l2) -> NoDup [].
h :: tl case:
(forall l1 l2, h :: tl = l1 ++ l2 -> Disjoint l1 l2) -> NoDup (h :: tl).
This is what you've got above (modulo the renaming). For the second case you are also getting the induction hypothesis, which we get from the original statement substituting tl for l:
(forall l1 l2, tl = l1 ++ l2 -> Disjoint l1 l2) -> NoDup tl.
Incidentally, the theorem is provable and you might find the following helper lemmas useful:
Lemma disjoint_cons_l {X} (h : X) l1 l2 :
Disjoint (h :: l1) l2 -> Disjoint l1 l2.
Admitted.
Lemma disjoint_singleton {X} h (l : list X) :
Disjoint [h] l -> ~ In h l.
Admitted.

How to use a custom induction principle in Coq?

I read that the induction principle for a type is just a theorem about a proposition P. So I constructed an induction principle for List based on the right (or reverse) list constructor .
Definition rcons {X:Type} (l:list X) (x:X) : list X :=
l ++ x::nil.
The induction principle itself is:
Definition true_for_nil {X:Type}(P:list X -> Prop) : Prop :=
P nil.
Definition true_for_list {X:Type} (P:list X -> Prop) : Prop :=
forall xs, P xs.
Definition preserved_by_rcons {X:Type} (P: list X -> Prop): Prop :=
forall xs' x, P xs' -> P (rcons xs' x).
Theorem list_ind_rcons:
forall {X:Type} (P:list X -> Prop),
true_for_nil P ->
preserved_by_rcons P ->
true_for_list P.
Proof. Admitted.
But now, I am having trouble using the theorem. I don't how to invoke it to achieve the same as the induction tactic.
For example, I tried:
Theorem rev_app_dist: forall {X} (l1 l2:list X), rev (l1 ++ l2) = rev l2 ++ rev l1.
Proof. intros X l1 l2.
induction l2 using list_ind_rcons.
But in the last line, I got:
Error: Cannot recognize an induction scheme.
What are the correct steps to define and apply a custom induction principle like list_ind_rcons?
Thanks
If one would like to preserve the intermediate definitions, then one could use the Section mechanism, like so:
Require Import Coq.Lists.List. Import ListNotations.
Definition rcons {X:Type} (l:list X) (x:X) : list X :=
l ++ [x].
Section custom_induction_principle.
Variable X : Type.
Variable P : list X -> Prop.
Hypothesis true_for_nil : P nil.
Hypothesis true_for_list : forall xs, P xs.
Hypothesis preserved_by_rcons : forall xs' x, P xs' -> P (rcons xs' x).
Fixpoint list_ind_rcons (xs : list X) : P xs. Admitted.
End custom_induction_principle.
Coq substitutes the definitions and list_ind_rcons has the needed type and induction ... using ... works:
Theorem rev_app_dist: forall {X} (l1 l2:list X),
rev (l1 ++ l2) = rev l2 ++ rev l1.
Proof. intros X l1 l2.
induction l2 using list_ind_rcons.
Abort.
By the way, this induction principle is present in the standard library (List module):
Coq < Check rev_ind.
rev_ind
: forall (A : Type) (P : list A -> Prop),
P [] ->
(forall (x : A) (l : list A), P l -> P (l ++ [x])) ->
forall l : list A, P l
What you did was mostly correct. The problem is that Coq has some trouble recognizing that what you wrote is an induction principle, because of the intermediate definitions. This, for instance, works just fine:
Theorem list_ind_rcons:
forall {X:Type} (P:list X -> Prop),
P nil ->
(forall x l, P l -> P (rcons l x)) ->
forall l, P l.
Proof. Admitted.
Theorem rev_app_dist: forall {X} (l1 l2:list X), rev (l1 ++ l2) = rev l2 ++ rev l1.
Proof. intros X l1 l2.
induction l2 using #list_ind_rcons.
I don't know if Coq not being able to automatically unfold the intermediate definitions should be considered a bug or not, but at least there is a workaround.